Mitochondrial Fragmentation and Dysfunction in Type IIx/IIb Diaphragm Muscle Fibers in 24-Month Old Fischer 344 Rats - Brown, Alyssa D.; Davis, Leah A.; Fogarty, Matthew J.; Sieck, Gary C. (Frontiers in Physiology, 2021)
Sarcopenia is characterized by muscle fiber atrophy and weakness, which may be associated with mitochondrial fragmentation and dysfunction. Mitochondrial remodeling and biogenesis in muscle fibers occurs in response to exercise and increased muscle activity. However, the adaptability mitochondria may decrease with age. The diaphragm muscle (DIAm) sustains breathing, via recruitment of fatigue-resistant type I and IIa fibers. More fatigable, type IIx/IIb DIAm fibers are infrequently recruited during airway protective and expulsive behaviors. DIAm sarcopenia is restricted to the atrophy of type IIx/IIb fibers, which impairs higher force airway protective and expulsive behaviors. The aerobic capacity to generate ATP within muscle fibers depends on the volume and intrinsic respiratory capacity of mitochondria. In the present study, mitochondria in type-identified DIAm fibers were labeled using MitoTracker Green and imaged in 3-D using confocal microscopy. Mitochondrial volume density was higher in type I and IIa DIAm fibers compared with type IIx/IIb fibers. Mitochondrial volume density did not change with age in type I and IIa fibers but was reduced in type IIx/IIb fibers in 24-month rats. Furthermore, mitochondria were more fragmented in type IIx/IIb compared with type I and IIa fibers, and worsened in 24-month rats. The maximum respiratory capacity of mitochondria in DIAm fibers was determined using a quantitative histochemical technique to measure the maximum velocity of the succinate dehydrogenase reaction (SDHmax). SDHmax per fiber volume was higher in type I and IIa DIAm fibers and did not change with age. In contrast, SDHmax per fiber volume decreased with age in type IIx/IIb DIAm fibers. There were two distinct clusters for SDHmax per fiber volume and mitochondrial volume density, one comprising type I and IIa fibers and the second comprising type IIx/IIb fibers. The separation of these clusters increased with aging. There was also a clear relation between SDHmax per mitochondrial volume and the extent of mitochondrial fragmentation. The results show that DIAm sarcopenia is restricted to type IIx/IIb DIAm fibers and related to reduced mitochondrial volume, mitochondrial fragmentation and reduced SDHmax per fiber volume.